Hukum Kasualitas Jatuhnya Talak dan Masa Iddah:: Studi Perbandingan Hukum di Indonesia dan Arab Saudi - Syariv, Rizki Adzaky; Rouf , Abd. (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2025)
This study examines the causality of divorce (ṭalāq) and the commencement of the waiting period (ʿiddah) from the perspectives of Indonesia’s positive legal system and the classical fiqh underpinning the legal system of Saudi Arabia. Using a normative-comparative approach, the research analyzes primary legal sources such as Indonesia’s Law No. 1 of 1974, the Compilation of Islamic Law (KHI), and Saudi Arabia’s Personal Status Law, as well as secondary sources drawn from classical fiqh literature across the four Sunni madhhabs. The findings indicate that in Indonesia, a divorce is legally valid only when declared before a Religious Court, and the ʿiddah period begins upon the court’s ruling. In contrast, Saudi law recognizes divorce pronounced directly by the husband without formal court proceedings, and the ʿiddah starts immediately upon such pronouncement. These contrasting approaches reflect differing emphases on legal certainty and the protection of women's rights. The study recommends an integrative understanding between state law and classical fiqh to ensure family law policies are more responsive to contemporary social realities and Islamic justice values.